Pediatric neurosurgery AC-after COVID-19: What has really changed? A review of the literature - Noris, Alice; Peraio, Simone; Di Rita, Andrea; Ricci, Zaccaria; Spezzani, Chiara; Lenge, Matteo; Giordano, Flavio (Frontiers in Pediatrics, 2022)
The COVID-19 outbreak has dramatically changed the organization of Pediatric Neurosurgery all over the world. The Departments involved developed similar plans to maintain emergency surgery without reducing the clinical activities. The Association of Pediatric Neurosurgeons wrote different memoranda to enlist the surgical procedures not to be postponed with special attention to high-risk pathology for COVID-19 contamination like trans-naso-sphenoidal surgery. On this basis, we have conducted a complete literature review focusing upon many topics: hospital organization; patients and parents screening; surgical indication criteria; outpatient clinic and teleconsultation; telematic conference and meeting; fellowship and training; virtual multidisciplinary meeting.